2009
DOI: 10.1140/epjb/e2009-00407-9
|View full text |Cite
|
Sign up to set email alerts
|

LCAO model for 3D Fermi surface of high-Tc cuprate Tl2Ba2CuO6+δ

Abstract: A simple analytical formula for three-dimensional Fermi surface (3D FS) of Tl2Ba2CuO 6+δ is derived in the framework of LCAO approximation spanned over Cu 4s, Cu 3d x 2 −y 2 , O 2px and O 2py states. This analytical result can be used for fitting of experimental data for 3D FS such as polar angle magnetoresistance oscillation. The model takes into account effective copper-copper hopping amplitude tss between Cu 4s orbitals from neighbouring CuO2 layers. The acceptable correspondence with the experimental data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…4). We may note that band structures calculated for bilayers Bi-2212 [47,75], Tl-2201 [45], tri-layer Tl-2223 and four-layer Tl-2234 [76] revealed that the dominant interlayer hopping exhibits a γ 2 -modulation, too. In addition, Chakravarty et al [77] assumed the same γ 2 -modulation However, this perturbative treatment yields a tightbinding model different from the one of Ref.…”
Section: Analytical Approach: Microscopical Origin Of the Effective H...mentioning
confidence: 91%
See 2 more Smart Citations
“…4). We may note that band structures calculated for bilayers Bi-2212 [47,75], Tl-2201 [45], tri-layer Tl-2223 and four-layer Tl-2234 [76] revealed that the dominant interlayer hopping exhibits a γ 2 -modulation, too. In addition, Chakravarty et al [77] assumed the same γ 2 -modulation However, this perturbative treatment yields a tightbinding model different from the one of Ref.…”
Section: Analytical Approach: Microscopical Origin Of the Effective H...mentioning
confidence: 91%
“…This model has also been used in order to fit the experimental out-of-plane Fermi surface of overdoped LSCO (δ = 0.22) obtained with ARPES [41]. In addition, a three-dimensional (3D) fourband tight-binding model was derived by Mishonov et al [45] in order to explain the observation of the 3D Fermi surface in Tl 2 Ba 2 CuO 6+δ [60].…”
Section: Emery and Related Microscopical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe, however, that Bi 2 Sr 2 CaCu 2 O 8 , which is easily cleaved by adhesive tape surfaces, will catalyze the development of Cooper pair mass spectroscopy. Here we have to point out that the electron band structure of over-doped high-T c cuprates is easily fitted by Linear Combination of Atomic Orbital (LCAO) method [10][11][12]. The discrepancy between the corresponding integral for optical mass that can be easily calculated and the experimentally determined Cooper pair mass will reveal how good we understand the effects of strong correlations.…”
Section: * *mentioning
confidence: 99%
“…Here we have to point out that the electron band structure of over-doped high-T c cuprates is easily fitted by Linear Combination of Atomic Orbital (LCAO) method. [5][6][7] The discrepancy between the corresponding integral for optical mass that can be easily calculated and the experimentally determined Cooper pair mass will reveal how good we understand the effects of strong correlations. We suppose for the pnictide superconductors the situation is the same.…”
mentioning
confidence: 99%